2018
DOI: 10.3390/foods7120199
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bioactive Compounds, Mineral Content and Antioxidant Capacity in Bean Varieties Grown in Semi-Arid Conditions in Zacatecas, Mexico

Abstract: This research describes the characterization of bioactive compounds, mineral content, and antioxidant capacity in bean varieties grown in semi-arid conditions in Zacatecas, Mexico. This will provide better progress perspectives for agriculture nationwide and will ensure that bean crops are in the condition to satisfy the population’s nutritional needs by placing it not only as one of the foodstuffs comprising Mexico’s basic diet but also as one of the legumes having greater biofortification potential in Mexico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
10
5
1
Order By: Relevance
“…It should be noted that within the CIELCH color model, the lower values associated with C * indicate a lower color purity, while higher values (close to 50) represent a purer color. Therefore, the lower the saturation of a given color, the greater the grayish hue and discoloration [47]. These results were similar to those reported by Vera-Guzmán et al [44], who reported L * values in a range from 21.8 to 52.8 in wild genotypes of Capsicum annuum L cultivated in Oaxaca, Mexico.…”
Section: Fruit Colorsupporting
confidence: 90%
See 1 more Smart Citation
“…It should be noted that within the CIELCH color model, the lower values associated with C * indicate a lower color purity, while higher values (close to 50) represent a purer color. Therefore, the lower the saturation of a given color, the greater the grayish hue and discoloration [47]. These results were similar to those reported by Vera-Guzmán et al [44], who reported L * values in a range from 21.8 to 52.8 in wild genotypes of Capsicum annuum L cultivated in Oaxaca, Mexico.…”
Section: Fruit Colorsupporting
confidence: 90%
“…It should be noted that within the CIELCH color model, the lower values associated with C * indicate a lower color purity, while higher values (close to 50) represent a purer color. Therefore, the lower the saturation of a given color, the greater the grayish hue and discoloration [47]. The hue angle (h *) readings were found in the range from 32.04 to 51.91 (Table 3), according to these values, the color of the analyzed samples is red-yellow, a tone that is associated with a h * value of 90° on the hue circle.…”
Section: Fruit Colormentioning
confidence: 97%
“…This dose was better than the 200 ppm dose where 55% scavenging activity was obtained. Similar percentages were reported by SANCHEZ et al (2017) and HERRERA-HERNÁNDEZ et al (2018) who found values ranged from 45-80% scavenging activity in biofortification studies in beans.…”
Section: Antioxidant Capacitysupporting
confidence: 89%
“…Zn and Fe are essential mineral elements for human health and were exceptionally high in the PL-005 and PL-014 populations of P. lunatus, the PC-022 population of P. coccineus and the PV-003 population of the control species P. vulgaris, with 3.88 to 4.49 and 5.62 to 7.38 mg 100 g -1 Zn and Fe, respectively (Table 5). These values are lower than the Fe content reported by Seidu et al (2015) and Palupi et al (2022) in P. lunatus but within the ranges of Fe and Zn in P. vulgaris reported by Herrera-Hernández et al (2018).…”
Section: Discussionsupporting
confidence: 67%